System identification, finite element modelling, and wind-induced vibration control of the Smáratorg building in Reykjavik, Iceland. - Dagur Hrafn Pálsson 1994- (2022)
The focus of this thesis is to assess the dynamic characteristics of 21 storey building, Smáratorg, in Reykjavik. The building is known to be sensitive to wind-induced vibrations. Vibration measurements taken from three floors of the building during past earthquakes are used to identify the dynamic properties of the building such as its vibration frequencies and damping ratios. A detailed finite element model of the building is prepared, and the model is updated with dynamic properties obtained from system identification using earthquake-induced vibration measurements. The updated model is verified by simulating its seismic response to ground motion recorded at its basement, and comparing the simulated results with corresponding vibrations recorded at two different floors. The results show that the system identification provides reliable estimates of the dynamic properties of the structure, and that the model adequately simulates recorded seismic response. The updated model is then used to simulated wind-induced response of the building. Using several relevant scenarios of wind forces, floor accelerations of the building are estimated by performing dynamic time history analysis of the finite element model. Simulation results show that floor accelerations during strong winds could exceed comfort limit of the occupants. To reduce wind-induced floor accelerations, a passive tuned mass damper is placed at the top floor of the numerical model of the building. The parameters of the tuned mass damper are optimized to minimize wind-induced vibrations by tuning the damper to the appropriate vibration mode of the building. Wind response of the building with and without tuned mass damper was compared. The results show that the tuned mass damper can significantly reduce both peak and root mean square floor acceleration of the building, and therefore offer potential mitigation measure for the building. The results also show that, tuned mass dampers, while very effective in controlling wind response, are not very effective in ...